2019
DOI: 10.1158/1078-0432.ccr-18-2953
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Characterization of Human Thyroid Cancer Cell Lines: A Validated Panel for Preclinical Studies

Abstract: Purpose: Thyroid cancer cell lines are valuable models but have been neglected in pancancer genomic studies. Moreover, their misidentification has been a significant problem. We aim to provide a validated dataset for thyroid cancer researchers. Experimental Design: We performed next-generation sequencing (NGS) and analyzed the transcriptome of 60 authenticated thyroid cell lines and compared our findings with the known genomic defects in human thyroid cancers. Results: Unsupervised transcriptomic analysis show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
123
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 44 publications
13
123
0
Order By: Relevance
“…2B). These results are consistent with our Affymetrix gene expression data, showing expression of RET in the CUTC48 cells, as well as next-generation sequencing (25). We next performed Western blot analysis to evaluate RET/PTC1 protein expression in the CUTC48 cells, using the TPC1 cells as a positive control for RET/PTC1 expression, the HTh74 cells as a negative control, and the lung cancer cell lines Calu6, DMS-53, and H889, to monitor full length RET expression.…”
Section: Identification Of the Ret/ptc1 Rearrangement In The Cutc48 Csupporting
confidence: 92%
See 3 more Smart Citations
“…2B). These results are consistent with our Affymetrix gene expression data, showing expression of RET in the CUTC48 cells, as well as next-generation sequencing (25). We next performed Western blot analysis to evaluate RET/PTC1 protein expression in the CUTC48 cells, using the TPC1 cells as a positive control for RET/PTC1 expression, the HTh74 cells as a negative control, and the lung cancer cell lines Calu6, DMS-53, and H889, to monitor full length RET expression.…”
Section: Identification Of the Ret/ptc1 Rearrangement In The Cutc48 Csupporting
confidence: 92%
“…Interestingly, the CUTC60 cell line was resistant to BRAF (dabrafenib and vemurafenib IC 50 > 10 mmol/L) and MEK1/2 (selumetinib, PD-0325901, and trametinib IC 50 s > 9 mmol/L) inhibitors despite the presence of BRAF V600E mutation ( Supplementary Table S1). We have recently reported that the TCGA-derived BRAFV600E-RAS score (BRS) is a better predictor of MAPK pathway dependence than BRAF mutational status (6,25). Consistent with this, the CUTC5 cells have a lower BRS than the CUTC60 cells (CUTC5 BRS ¼ À0.341 vs. CUTC60 BRS ¼ 0.089), indicating the CUTC60 cells are less reliant on the MAPK pathway and, thus, resistant to MEK1/2 or BRAF inhibition.…”
Section: The Sensitivity Of Cutc Cell Lines To Kinase Inhibitorsmentioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, of the twelve skin samples in this cluster that were annotated by Tsoi et al, all three of the skin cell lines and seven of the nine skin tumors were annotated as being of an 'undifferentiated' subtype 41 . The majority (11/12) of the thyroid cell lines, which have been observed to be more dedifferentiated than thyroid tumors 34,45,46 , also belonged to this cluster. To further assess how distinct these cell line models are from their lineage-matched counterparts that co-clustered with tumors, we also looked at a set of lineagespecific transcription factors.…”
Section: Cell Lines In This Cluster Lacked Lineage-specific Expressiomentioning
confidence: 93%